Reworking of the Gangdese magmatic arc, southeastern Tibet: post‐collisional metamorphism and anatexis. (5th November 2014) - Zhang, Z.; Dong, X.; Xiang, H.; Ding, H.; He, Z.; Liou, J. G.
Abstract The Gangdese magmatic arc, southeastern Tibet, was built by mantle‐derived magma accretion and juvenile crustal growth during the Mesozoic to Early Cenozoic northward subduction of the Neo‐Tethyan oceanic slab beneath the Eurasian continent. The petrological and geochronological data reveal that the lower crust of the southeastern Gangdese arc experienced Oligocene reworking by metamorphism, anatexis and magmatism after the India and Asia collision. The post‐collisional metamorphic and migmatitic rocks formed at 34–26 Ma and 28–26 Ma respectively. Meta‐granitoids have protolith ages of 65–38 Ma. Inherited detrital zircon from metasedimentary rocks has highly variable ages ranging from 2708 to 37 Ma. These rocks underwent post‐collisional amphibolite facies metamorphism and coeval anatexis under P–T conditions of 710–760 °C and 12 kbar with geothermal gradients of 18–20 °C km−1, indicating a distinct crustal thickening process. Crustal shortening, thickening and possible subduction erosion due to the continental collision and ongoing convergence resulted in high‐P metamorphic and anatectic reworking of the magmatic and sedimentary rocks of the deep Gangdese arc. This study provides a typical example of the reworking of juvenile and ancient continental crust during active collisional orogeny.